1996
DOI: 10.1086/117968
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space Telescope WFPC2 Imaging of M16: Photoevaporation and Emerging Young Stellar Objects

Abstract: We present Hubble Space Telescope WFPC2 images of elephant trunks in the H II region M16. There are three principle results of this study. First, the morphology and stratified ionization structure of the interface between the dense molecular material and the interior of the H II region is well understood in terms of photoionization of a photoevaporative flow. Photoionization models of an empirical density profile capture the essential features of the observations, including the extremely localized region of [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
243
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(262 citation statements)
references
References 35 publications
18
243
1
Order By: Relevance
“…The gas pressure inferred from Hubble observations of the optical line emission from the faint end of the photo-evaporation flows arising from pillar I is p/k ∼ 10 7 K cm −3 (see Fig. 7b, abscissa 0 in Hester et al 1996). This value sets an upper limit on the ambient pressure around the flows, which is lower than the pressure required for the collisional heating solution.…”
Section: Collisional Heating Of Dustmentioning
confidence: 88%
See 1 more Smart Citation
“…The gas pressure inferred from Hubble observations of the optical line emission from the faint end of the photo-evaporation flows arising from pillar I is p/k ∼ 10 7 K cm −3 (see Fig. 7b, abscissa 0 in Hester et al 1996). This value sets an upper limit on the ambient pressure around the flows, which is lower than the pressure required for the collisional heating solution.…”
Section: Collisional Heating Of Dustmentioning
confidence: 88%
“…The Eagle Nebula (M 16) is a nearby (d = 2.0 ± 0.1 kpc, Hillenbrand et al 1993) massive-star forming region that has become an icon since the publication of spectacular Hubble Space Telescope (HST) images of its ionized gas emission (Hester et al 1996). As one of the nearest star-forming regions and one of the most well-observed across the electromagnetic spectrum, the Eagle Nebula is a reference source.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamical interactions among fragments or protostars in a massive core could lead to the ejection of some of them, which prematurely halts their accretion (Reipurth & Clarke 2001;Boss 2001;Bate et al 2002Bate et al , 2003Goodwin et al 2004;Umbreit et al 2005;Bate 2011). Photoionizing radiation from massive OB stars might contribute by removing much of the envelope and disk of a low-mass protostar (Hester et al 1996;Kroupa & Bouvier 2003a;Whitworth & Zinnecker 2004). Alternatively, turbulent compression and fragmentation of gas in a molecular cloud produces collapsing cores over a wide range of masses (Padoan & Nordlund 2002, 2004Hennebelle & Chabrier 2008;Elmegreen 2011).…”
Section: Theory: Star-like Bd Formationmentioning
confidence: 99%
“…In low-mass star-forming regions, which typically form objects in groups or loose associations, the main brown dwarf formation mechanisms are turbulent fragmentation (Padoan & Nordlund 2004;Hennebelle & Chabrier 2008) and ejection from multiple protostellar systems and/or fragmented disks (Reipurth & Clarke 2001;Bate et al 2002;Matzner & Levin 2005;Whitworth & Stamatellos 2006). However, in the surroundings of high-mass stars, where objects typically form in a more tightly packed manner, there are additional mechanisms, namely photo-evaporation of cores near massive stars (e.g., Hester et al 1996;Whitworth & Zinnecker 2004) that have already been observed in young clusters (see e.g., Bouy et al 2009;Hodapp et al 2009), and gravitational fragmentation of dense filaments formed in a nascent cluster (e.g., Bonnell et al 2008;Bate 2012).…”
Section: Introductionmentioning
confidence: 99%